If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 5) = 2(2x + 9) Reorder the terms: 3(5 + x) = 2(2x + 9) (5 * 3 + x * 3) = 2(2x + 9) (15 + 3x) = 2(2x + 9) Reorder the terms: 15 + 3x = 2(9 + 2x) 15 + 3x = (9 * 2 + 2x * 2) 15 + 3x = (18 + 4x) Solving 15 + 3x = 18 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 15 + 3x + -4x = 18 + 4x + -4x Combine like terms: 3x + -4x = -1x 15 + -1x = 18 + 4x + -4x Combine like terms: 4x + -4x = 0 15 + -1x = 18 + 0 15 + -1x = 18 Add '-15' to each side of the equation. 15 + -15 + -1x = 18 + -15 Combine like terms: 15 + -15 = 0 0 + -1x = 18 + -15 -1x = 18 + -15 Combine like terms: 18 + -15 = 3 -1x = 3 Divide each side by '-1'. x = -3 Simplifying x = -3
| X^2-16z+64=0 | | 2m^2-7m-30=0 | | ln(x+6)-ln(x+5)=1 | | y=2.5-.06x | | -27=18-5x-4x | | .25(x-2)=17+2x | | x^2+12x+15=4 | | 18+4.50x=12+5.75x | | 3s+10=28 | | 4x-6x-12=-2x+7-12 | | 4x-6x-12=-2c+7-12 | | (8x-9)(9x+2)=0 | | 580/200x | | 200/580 | | E=20t | | 5/9*9/5 | | -7=11/17s | | 3s+40=112 | | 5/9*1664.1 | | -y^2-y-3=0 | | 36=0.6x | | -6x+4=2(4-x) | | 5x-2x-8=13 | | 3x^2+5y-6=0 | | sen(5x)-sen(3x)-sen(x)=0 | | 6s+-6=s+14 | | -2(a-8)=36 | | 16(1/2x)4 | | 3m^3=27m^3 | | T=4033/33000*.021 | | 4-3+10=101 | | 0.9ln(10000-0.01D)+0.1ln(10000-7000+0.99D)= |